Vibration Analysis of Winding Hoisting System based on ADAMS/Cable. Issue 1 (January 2021) - Ma, Chi; Yao, Jiannan; Xiao, Xinming; Di, Xiao; Jiang, Yuqiang
Abstract: In order to study the lateral vibration characteristics of the vertical wire rope of the winding hoisting system, a virtual prototype model including drum, wire rope, head sheaves and guides is established by ADAMS/Cable module. Dynamic simulation of winding hoisting process is carried out by external solution with ADAMS/Solver simulation control language. The validity of the model is verified with a winding hoisting test-bed, the dynamic behavior of the hoisting system under variable speed conditions is analyzed, and the lateral vibration law and the influence on the longitudinal vibration of the suspension rope under the speed change are obtained.